2020
DOI: 10.1167/tvst.9.2.35
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Learning for Automated OCTA Detection of Diabetic Retinopathy

Abstract: To test the feasibility of using deep learning for optical coherence tomography angiography (OCTA) detection of diabetic retinopathy. Methods: A deep-learning convolutional neural network (CNN) architecture, VGG16, was employed for this study. A transfer learning process was implemented to retrain the CNN for robust OCTA classification. One dataset, consisting of images of 32 healthy eyes, 75 eyes with diabetic retinopathy (DR), and 24 eyes with diabetes but no DR (NoDR), was used for training and cross-valida… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 39 publications
0
55
0
Order By: Relevance
“…Device implementation of image alignment and tracking for longitudinal data will better serial assessment of progressive retinal diseases, including AMD and DR. As these improvements become commercially available, the clinical applicability and utility of OCTA will continue to expand and could have lasting implications in the way we image the retinal vasculature. Moreover, application of machine learning to OCTA will yield insights into new pathologic signals that were previously overlooked that could greatly impact the clinical management of retinal disease [ 89 , 90 ].…”
Section: The Future Of Octamentioning
confidence: 99%
“…Device implementation of image alignment and tracking for longitudinal data will better serial assessment of progressive retinal diseases, including AMD and DR. As these improvements become commercially available, the clinical applicability and utility of OCTA will continue to expand and could have lasting implications in the way we image the retinal vasculature. Moreover, application of machine learning to OCTA will yield insights into new pathologic signals that were previously overlooked that could greatly impact the clinical management of retinal disease [ 89 , 90 ].…”
Section: The Future Of Octamentioning
confidence: 99%
“…Deep learning algorithms have also been applied recently to retinal optical coherence tomography (OCT) and OCT angiography (OCTA) images for automated diagnosis of DR, because these imaging techniques provide higher sensitivity to detect early diabetic retinal changes [28]. Diagnostic accuracy studies have not been published yet, but preliminary internal validation tests show comparable diagnostic accuracy to the one using fundus images: Sandhu et al [29] reported their algorithm to have sensitivity of 93% and specificity of 95%, and the work of Li et al [30] achieved a sensitivity of 90% and specificity of 95%; using OCTA images, sensitivity of 98% and specificity of 87% were reported by Sandhu et al [31], and the system of Le et al [32] achieved 84% sensitivity and 91% specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the existing works focused on the diagnosis of AMD using OCT or Color Fundus Photography. Moreover, published works on OCTA images involved other retinal diseases such as Diabetic Retinopathy (DR) [17].…”
Section: Cnn Architecture and Transfer Learningmentioning
confidence: 99%
“…Results showed a ROC-AUC of 0.89 at the B-scan levels and 0.91 for volumes. Hwang et al [22] In what concerns the use of OCTA in DL, Le et al [17] tested the feasibility of using DL for DR detection from OCTA including 77 patients and 20 control subjects. The authors applied transfer learning on a VGG16 network for robust OCTA classification.…”
Section: Cnn Architecture and Transfer Learningmentioning
confidence: 99%